Evaluation of Kenten Main Substation Grounding System Based on IEEE 80-2013 - Muhammad Abu Bakar Sidik; Muhammad Irfan Jambak; Amir Arifin; Momon Sodik Imanudin; Syarifah Fitria; Dodo Nugraha; Muhammad Alif Wicaksono (Jurusan Teknik Elektro Fakultas Teknik Universitas Sriwijaya, 2024)
Grounding system in a Substation has an important role in human and equipment safety therefore the grounding system condition should always be under observation. Maintenance and evaluation regularly should be carried out in line with the possibility of fault current increasing that embark in the system and disturbances from lightning strokes. In this study, the grounding system at the Kenten substation was analysed by using an analytic calculation method and a numerical method software. The calculation was based on IEEE Std. 80-2013 (IEEE Guide for Safety in AC Substations Grounding). From the study, it was obtained that the grounding system of Kenten substation just fulfils the safety standard regulation.